Research on the movement process of erosion-denudation type debris flow in middle-low mountains based on particle algorithm model - He, Xiaofeng; Gong, Yongfeng; Yan, Jinkai; Gao, Shichang; He, Zheng; Zhang, Gang; Wang, Guorui; Hu, Zhiyong; Wang, Hui (Frontiers in Earth Science, 2025)
Debris flow is a significant geological hazard in the mountainous regions of China, characterized by its sudden onset, high mobility, and considerable destructive potential. In the Helan Mountains, debris flows primarily consist of coarse-grained materials transported by water flows, exhibiting both high destructive potential and a broad impact range. Therefore, understanding the dynamics of debris flows in this region is of crucial importance. This study focuses on the Zhengguangou debris flow, utilizing the DAN-3D software based on Smoothed Particle Hydrodynamics (SPH) to construct a dynamic debris flow model. The movement characteristics of the debris flow were investigated by simulating various operating conditions, including differences in formation area conditions and rainfall intensity. The simulation results indicate that under extreme conditions (with a pore pressure coefficient of 0.8), the debris flow with the same initial volume traveled an average distance of 1503 m, significantly farther than the 1323 m travelled under normal conditions (with a pore pressure coefficient of 0.3). Under normal conditions, the final average deposition thickness of the debris flow was 8.9 m, which was thicker than the 8.3 m observed under extreme conditions. Regarding movement speed, the debris flow initially accelerated and then decelerated, with the extreme condition resulting in a greater travel distance compared to the normal condition. Additionally, the debris flow exhibited greater erosion depth and volume under normal conditions. In contrast, under extreme conditions, the debris flow had a larger scraping width, with the maximum width occurring at the point where the flow direction changed. This study enhances our understanding of the dynamic characteristics of debris flows in northern Ningxia and provides valuable insights for hazard prediction and mitigation efforts in the region.